Compelling palatability of flavoring Atractus AQVA (R) for Nile tilapia juveniles - Sanches Alves, Denis Rogerio; Oliveira, Suzana Raquel de; Sosa, Bruno dos Santos [UNESP]; Boscolo, Wilson Rogerio; Signor, Altevir; Bittencourt, Fabio (Univ Catolica De Valparaiso, 2020)
This study determined the compelling palatability of Atractus AQVA (R) flavoring for Nile tilapia juveniles (Oreochromis niloticus). Five isoproteic (40% crude protein) and isoenergetic (3,420 kcal kg(-1)) experimental diets were elaborated containing 0.25 (A25), 0.50 (A50) and 0.75% (A75) flavoring inclusion, a positive control diet with 10% fishmeal (FPE) and a negative control without fishmeal (SPE). Five juvenile individuals (2.58 +/- 0.27 g) were distributed in five 10 L tanks and were fed four times a day with one of the diets, randomly raffled. The same number of pellets was offered, and the following behaviors were observed: time to capture the first pellet, number of pellet rejections, and number of approximations without capture and consumed pellets in each feeding event, using three-minute recordings with a digital camera. A significant effect (P < 0.05) was found regarding the number of approximations without capturing the pellet, as well as a higher palatability index for A75, followed by A50, A25, SPE and FPE. Therefore, it was concluded that A75 provided the highest compelling palatability of all diets by increasing the palatability index by 10.49% and displaying a 23.13% reduced rejection of pellets, besides presenting a 3.3 fold reduction in the number of approximations without capturing pellets with diet FPE.
Keywords: Oreochromis niloticus; tilapia; fish farm; feeding preference; nutrition